The Transcending Age: A Study of Psycho-social Wellbeing of Elderly Women in India - Sabiha Hussain (Journal of Sociological Research, 2024)
India is witnessing rapid growth of elderly population. The population aged 60 years or older is projected to climb from 9% in 2015 to 19% in 2050 and to 32% in 2100 (UN, 2017). Aging population requires attention on their physical, social and emotional well-being. Wellbeing encompasses multiple interactive components which are beyond the conventional issues of health and diseases. There is multitude of social relationships and dynamics of social roles that women in this age negotiate in their lives. Family dynamics, compatibility with partner, household headship, decision making and level of autonomy, incidences of domestic violence, security concerns, care-giving, perceptions of self, societal status do influence quality of life and wellbeing. Using primary survey data of 165 women aged 60 to 65 years residing in urban areas in Delhi-National Capital Region (NCR) interviewed during first quarter of 2018, the paper attempts to understand what does well-being mean to them, how do they ensure it, what are the psycho-social barriers and how do they overcome them. Purposive sampling and snowballing techniques has been employed to identify these women. Increase in health related problems especially mobility issues, lifestyle diseases along with depression were predominant in this age. For women in post 60 years of age, respect and appreciation from family and society is vital to ensure their happiness, while family bonding and overall contentment stands out for ensuring wellbeing. Religious pursuits and social interaction are the fundamental coping mechanisms from stress. Inadequate and incomplete education and early marriage rooted in patriarchy and financial dependence are the principal sources of regret in lives of these women. Widowed women were identified as the most vulnerable. Women in the lowest income group and literacy level were further marginalized and needed help from state. Evident gaps were reported in the existing welfare government schemes for this age.